A contemporary analysis of survival for resected pancreatic ductal adenocarcinoma. Issue 1 (24th September 2012) - Lewis, Russell; Drebin, Jeffrey A.; Callery, Mark P.; Fraker, Douglas; Kent, Tara S.; Gates, Jenna; Vollmer, Charles M.
Abstract Introduction Survival after a resected pancreatic ductal adenocarcinoma (PDAC) appears to be improving. Yet, in spite of advancements, prognosis remains disappointing. This study analyses a contemporary experience and identifies features associated with survival. Methods Kaplan–Meier analysis was conducted for 424 PDAC resections performed at two institutions (2001–2011). Multivariate analysis was performed to elicit characteristics independently associated with survival. Results The median, 1‐, and 5‐year survivals were 21.3 m, 76%, and 23%, with 30/90‐day mortalities of 0.7%/1.7%. 76% of patients received adjuvant therapy. Patients with major complications (Clavien Grade IIIb‐IV) survived equivalently to patients with no complications (P = 0.33). The median and 5‐year survival for a total pancreatectomy was 32.2 m/49%; for 90 'favourable biology' patients (R0/N0/M0) was 37.3 m/40%; and for IPMN (9% of series) was 21.2 m/46%. Elderly (>75 yo) and nonelderly patients had similar survival. Favorable prognostic features by multivariate analysis include lower POSSUM physiology score, R0 resection, absence of operative transfusion, G1/G2 grade, absence of lymphovascular invasion, T1/T2 stage, smaller tumor size, LN ratio <0.3, and receipt of adjuvant therapy. Conclusion This experience with resected PDAC shows decreasing morbidity and mortality rates along with modestly improving long‐term survival, particularly for certain subgroups of patients. Survival is related to pathological features, pre‐operative physiology, operative results and adjuvant therapy.